Intracellular pressure controls the propagation of tension in crumpled cell membranes - Raviv Dharan; Avishai Barnoy; Andrey K. Tsaturyan; Alon Grossman; Shahar Goren; Inbar Yosibash; Dikla Nachmias; Natalie Elia; Raya Sorkin; Michael M. Kozlov (Nature Communications)
Abstract Propagation of membrane tension mediates mechanical signal transduction along surfaces of live cells and sets the time scale of mechanical equilibration of cell membranes. Recent studies in several cell types and under different conditions revealed a strikingly wide variation range of the tension propagation speeds including extremely low ones. The latter suggests a possibility of long-living inhomogeneities of membrane tension crucially affecting mechano-sensitive membrane processes. Here, we propose, analyze theoretically, and support experimentally a mechanism of tension propagation in membranes crumpled by the contractile cortical cytoskeleton. The tension spreading is mediated by the membrane flow between the crumples. We predict the pace of the tension propagation to be controlled by the intra-cellular pressure and the degree of the membrane crumpling. We provide experimental support for the suggested mechanism by monitoring the rate of tension propagation in cells exposed to external media of different osmolarities.